Interactive actions of Bdnf methylation and cell metabolism for building neural resilience under the influence of diet - Tyagi, Ethika (Neurobiol Dis, 2014)
Quality nutrition during the period of brain formation is a predictor of brain functional capacity and plasticity during adulthood; however it is not clear how this conferred plasticity imparts long-term neural resilience. Here we report that early exposure to dietary omega-3 fatty acids orchestrates key interactions between metabolic signals and Bdnf methylation creating a reservoir of neuroplasticity that can protect the brain against the deleterious effects of switching to a western diet (WD). We observed that the switch to a WD increased Bdnf methylation specific to exon IV, in proportion to anxiety-like behavior, in Sprague Dawley rats reared in low omega-3 fatty acid diet, and these effects were abolished by the DNA methyltransferase inhibitor 5-aza-2'-deoxycytidine. Blocking methylation also counteracted the reducing action of WD on the transcription regulator CTCF binding to Bdnf promoter IV. In vitro studies confirmed that CTCF binding to Bdnf promoter IV is essential for the action of DHA on BDNF regulation. Diet is also intrinsically associated to cell metabolism, and here we show that the switch to WD downregulated cell metabolism (NAD/NADH ratio and SIRT1). The fact that DNA methyltransferase inhibitor did not alter these parameters suggests they occur upstream to methylation. In turn, the methylation inhibitor counteracted the action of WD on PGC-1α, a mitochondrial transcription co-activator and BDNF regulator, suggesting that PGC-1α is an effector of Bdnf methylation. Results support a model in which diet can build an “epigenetic memory” during brain formation that confers resilience to metabolic perturbations occurring in adulthood.